Chemical processing of water-soluble species and formation of secondary organic aerosol in fogs. (1st March 2019) - Kim, Hwajin; Collier, Sonya; Ge, Xinlei; Xu, Jianzhong; Sun, Yele; Jiang, Wenqing; Wang, Youliang; Herckes, Pierre; Zhang, Qi
Abstract: A field study on fog chemistry and aqueous-phase processing of aerosol particles was conducted in Fresno, California's San Joaquin Valley (SJV) during wintertime. Fog droplets were collected while interstitial submicron aerosol was characterized in real time using a High Resolution Time-of-Flight Aerosol Mass Spectrometer (HR-AMS). The fog samples were later analyzed using HR-AMS, ion chromatography (IC), and total organic carbon analyzer (TOC). Compared to interstitial aerosol, dissolved solutes in fog waters were composed of higher fractions of ammonium, nitrate, sulfate, methanesulfonic acid, and oxygenated organic compounds, likely due to aqueous formation of secondary species as well as enhanced gas-to-particle partitioning of water-soluble gases under humid conditions. The low-volatility dissolved organic matter in fog water (F-OA) was moderately oxidized with an average oxygen-to-carbon (O/C) ratio of 0.42. The chemical composition of F-OA appeared to be overall similar to that of oxygenated organic component in interstitial aerosol (OOA) and the HR-AMS mass spectra of F-OA and OOA are highly similar (r 2 > 0.95). However, there are also significant chemical differences as F-OA appeared to contain a larger fraction of carboxylic functional groups than OOA, indicating enhanced organic acid formation through aqueous-phase reactions. In addition, F-OA was composed of substantially more nitrogen-containing compounds, with an average N/C ratio ∼4 times that of OOA. Most strikingly was that the F-OA spectra showed substantial enhancements of the Cx Hy N2 + (x ≥ 0; y ≥ 0) ions, which were likely contributed by imidazole- and/or pyrazine-based compounds formed from the aqueous reactions of aldehydes with amino compounds. The results of this study demonstrated that aqueous reactions in atmospheric droplets can significantly modify aerosol composition and contribute to the formation of oxygenated and nitrogen-containing organic compounds in atmospheric aerosol particles. This finding is important for understanding aerosol's effects on human health, air quality, and climate. Highlights: HR-AMS study of fog processing of PM1 in San Joaquin Valley of CA during winter. Fog waters are enriched of secondary inorganic and organic aerosol species. Organic residuals in fog waters (FOM) is moderately oxidized (average O/C = 0.42). FOM has more abundant carboxylic acid and organic nitrogen compounds than OOA. This is evidence for forming imidazole- or pyrazine-based compounds in fog waters.